ATLASES—THE NEW FASCINATION OF FRENCH PUBLISHERS - Jean Radvanyi (Geography, Environment, Sustainability)
Reacting to reader interest in publications of new types of atlases, many French authors and publishers rushed to occupy an emerging publishing niche and created a real fashion of small atlases attracting ever-greater public attention. The paper describes origins and features of this phenomenon.